The complete mitochondrial genome of the giant clam, Tridacna maxima (Tridacnidae Tridacna) - Haitao Ma; Yuehuan Zhang; Yang Zhang; Shu Xiao; Chenghui Han; Shixi Chen; Ziniu Yu (Mitochondrial DNA. Part B. Resources, 2019)
In this study, we present the first complete mitochondrial genome sequence of the giant clam Tridacna maxima. The total length of the mitogenome is 18,632 bp. It contains the typical mitochondrial genomic structure, including 13 protein-coding genes, 23 transfer RNA genes, 2 ribosomal RNA genes, and 1 control region (D-loop). Mitogenome base composition is biased toward A + T content, at 61.54%. A phylogenetic tree based on complete mitogenome sequences revealed that, within the genus Tridacna, T. maxima is closely related to T. squamosa and T. derasa.